ChemInform Abstract: Asymmetric Cascade Annulation Based on Enantioselective Oxa‐Diels—Alder Cycloaddition of in situ Generated Isochromenyliums by Cooperative Binary Catalysis of Pd(OAc)2 and (S)‐Trip. Issue 3 (21st January 2014) - Yu, Shu‐Yan; Zhang, Hao; Gao, Yang; Mo, Lei; Wang, Shaozhong; Yao, Zhu‐Jun
Abstract The newly developed methodology is applicable to a broad spectrum of substrates establishing dense multiple chiral centers including quaternary carbons of variable bridged ring systems.